Studies in stamina of judoists (2) - Sasa, T.; Asami, T.; Kaneko, M. (Association for the Scientific Studies on Judo, Kodokan, 1969)
Together with the training of technique, much importance has been laid, recently, on the cultivation of physical fitness in Judo, and various papers dealing with the subject have been reported. However, studies dealing with stamina in Judofrom the standpoint of respiratory and cardiovascular functions are very few. Stamina is a basic requirement in order to effect one's technique efficiently during a match. It is quite evident from the results of studies on the heart rate during Judo practice made by Ikai and Kaneko, and alsofrom measurements of energy exchange during execution of techniques in Judo made by Sugimoto and Ogawa that the practice of Judo imposes quite a load on the respiratory and cardiovascular systems. The present paper deals with a continuation of the study already reported last year, and was made in order to obtain further information regarding the stamina of Judoists. In the present study, also, such reactions as the heart rate and oxygen consumption were measured. Since only a few experimental subjects could be used due to technical difficulties the subjects used in the experiment were all well trained Judoists.